(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of product, price, and promotion on MSME competitiveness through purchase decisions in culinary MSMEs in Bekasi Regency. This research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 120 respondents selected using purposive sampling. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression, and mediation analysis using the Sobel test. The results indicate that product, price, and promotion have a positive and significant effect on purchase decisions, both partially and simultaneously, with promotion as the most dominant variable. Furthermore, purchase decisions have a positive and significant effect on MSME competitiveness. Mediation analysis reveals that purchase decisions significantly mediate the relationship between product, price, promotion, and MSME competitiveness. These findings suggest that effective marketing strategies not only directly influence competitiveness but also indirectly through improving consumer purchase decisions. This study implies that enhancing product quality, setting competitive pricing, and implementing effective promotional strategies are essential to improving the sustainable competitiveness of culinary MSMEs.